2022
DOI: 10.2337/dc21-2358
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Composition Is Predictive of Incident Type 2 Diabetes in a Population Cohort of 5,572 Finnish Adults

Abstract: OBJECTIVE To examine the previously unknown long-term association between gut microbiome composition and incident type 2 diabetes in a representative population cohort. RESEARCH DESIGN AND METHODS We collected fecal samples from 5,572 Finns (mean age 48.7 years; 54.1% women) in 2002 who were followed up for incident type 2 diabetes until 31 December 2017. The samples were sequenced using shotgun metagenomics. We examined asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…Previous studies have shown that Ruminococcus spp. is significantly associated with Crohn's disease, IBD, and type 2 diabetes (Hall et al, 2017;Baumgartner et al, 2021;Ruuskanen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Ruminococcus spp. is significantly associated with Crohn's disease, IBD, and type 2 diabetes (Hall et al, 2017;Baumgartner et al, 2021;Ruuskanen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We found that efflux pumps were the main mechanism of drug resistance in Firmicutes , Proteobacteria , Bacteroidetes , Verrucomicrobia , Synergistetes , Spirochaetes , and Actinobacteria . Notably, Firmicutes , Proteobacteria , and Bacteroidetes have been found to be dominant in the microbiota of mice and humans [ 27 ]. Therefore, we suspect that phorate causes hyperglycaemia in mice primarily by causing the dominant bacteria in the intestine to produce efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
“…The implications on health and disease have particularly fed the growing interest in the microbiome field with the possibility of using the microbiome profile as a novel tool for disease diagnostics and microbiome-informed personalized therapeutics in mind ( di Pierro, 2021 ; Zeevi et al, 2015 ). Moreover, recent studies show the potential of using the microbiome as a prognostic marker for disease progression, leading to personalized risk estimation ( Aasmets et al, 2021 ; Liu et al, 2022 ; Ruuskanen et al, 2022 ; H. Wang et al, 2022 ). Taken together, the microbiome carries relevant information about one’s health which can be exploited for the benefit of public well-being.…”
Section: Introductionmentioning
confidence: 99%